ELOC(TCEB1)-mutated renal cell carcinoma: a case report and clinicopathological analysis - Zhu, Yin; Fang, Mengchao; Wang, Shuo (Frontiers in Oncology, 2025)
ELOC (also referred to as TCEB1)-mutated renal cell carcinoma (ELOC-mutated RCC) is a rare, molecularly defined RCC newly incorporated into the 2022 5th Edition WHO Classification of Tumours of the Urinary and Male Genital Organs. It exhibits a broad histomorphological spectrum with overlapping features with clear cell RCC, posing diagnostic challenges and potential for misdiagnosis if not considered. This report presents a case initially diagnosed as CK7-positive RCC with fibromyomatous stroma (RCC-FMS). Next-generation sequencing (NGS) revealed a ELOC p.Y79C gene mutation in tumor cells, leading to the definitive diagnosis of ELOC-mutated RCC. Enhancing awareness of this rare tumor is crucial for improving diagnostic accuracy.